Modern concepts and methods in grade I mathematics a proposed syllabus for elementary school mathematics - Wichai Bunchua (1968)
A proposed syllabus about the modern concepts and methods in grade I mathematics is made to help teachers achieve the goal of showing the children the unified structure of all mathematics and introduce important concepts and vocabulary as early as possible in the best way that children can understand. The syllabus is intended to be a blend of basic ideas concerning mathematics itself and a method for presenting those ideas to children in meaningful ways.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Elementary) -- Philippines; Mathematical ability -- Testing; Mathematical ability in children